Enhancing Rural E-Governance through Improved Digital Access: A Case Study of Sudurpashchim Province, Nepal - Bhatt, Birendra Prasad (The Management Review, 2025)
This article investigates how improved digital access can foster effective rural e-governance in Sudurpashchim Province, Nepal. The province, marked by its geographical remoteness and limited infrastructure, continues to struggle with digital inclusion. A quantitative survey approach was employed, targeting 300 rural respondents selected via purposive sampling. The study assessed internet accessibility, ownership of digital devices, digital literacy, and usage of online government services. Findings indicate that only 35% of the population has consistent access to the internet, mainly through mobile phones, while 65% remain digitally excluded. Major barriers identified include limited connectivity, unaffordable digital tools, and lack of awareness or training. Additionally, respondents from digitally connected areas showed a higher tendency to use government services online, such as applying for official documents or accessing agricultural support. The research highlights how digital exclusion leads to a perpetuation of marginalization in public service delivery. To address this, the study proposes targeted policy interventions including the expansion of broadband networks, community-based training programs, and affordable device schemes. The findings offer valuable insights for policymakers aiming to strengthen inclusive e-governance in underdeveloped regions. This research contributes to the broader discourse on digital equity, public service innovation, and rural development through evidence-based policy recommendations.